Padrões de distribuição geográfica de lagartos (Reptilia, Squamata) na bacia do Rio Paraguai, América do Sul - Ribeiro, Ricardo Alexandre Kawashita (2015)
Search for geographic distribution patterns and understand of the processes that influence these patterns are concern of biogeography and ecology. Historical time-space processes and ecological constraints are agent that influences species distribution. Identification of biotic components helps the recognition of the endemism areas, which are useful to propose hypothesis about biogeographic historic events and to predict the influences of global climate changes on species. Climate changes are considered as the main threat to the biodiversity, especially in wetlands, which are highly dependent on temperature and rainfall for regulation of their dynamic. The main goal of this study was to investigate the existence of biotic components of lizards in the Paraguay River Basin, central South America and also to assess potential effects of the future global climate changes on populations of lizards in a wetland areas of the Humid Chaco and Pantanal, using species distribution modeling of Gymnophthalmidae lizards. The Paraguay River Basin (PRB) is the second largest river basin in South America, situated in the center of aforemencioned continent. In the PRB several ecoregions are presents, including two South American large wetlands, the Humid Chaco and the Pantanal. We obtained occurrence data of lizards by consulting the scientific collections and literature that were georeferenced with higher possible level of accuracy. We used biotic elements and endemicity analysis with occurrence data arranged in grids with 1°X1° and 2°X2 ° cells size that overlapping on the PRB area to identify biotic components. In the species distribution modeling analysis, we used occurrence of data of all known geographic range of five Gymnophthalmidae lizards. We made consensus models with ensemble forecasting criteria from BIOCLIM, DOMAIN, MAXENT, SVM and GLM algorithms, with current climate projections and for two future scenarios, RCP 2.6 and RCP 8.5. We obtained 4718 records of 80 species of lizards from PRB. We detected five groups with significant distribution that corroborated the predictions of vicariance model with biotic elements analysis with grid 1°X1° and 2°X2° cells size. We detected four areas of endemism with grid 1°X1° and six areas of endemism with 2°X2° cell size with endemicity analysis. Historical events like the young geological age with recent climatic stability, combined with current environmental instability, mainly generated by the flood pulse in the Pantanal, may have more intense role on the extinction and dispersal patterns than on speciation of the species. The PRB is composed by different biotic components that are influenced by major biogeographic units. Species distribution models consensus suggest the expansion of the distribution areas for future projections to the most lizards on moist wetland areas of the Humid Chaco and Pantanal. Considering that modeled species in this study inhabit dry micro-habits, the expansion in the distribution of lizards on the wetlands detected here, could mean reducing on the area of wetland in these ecoregions. However, global climate models (GCM) have weak prediction on hydrological changes, so the magnitude of the impacts in the wetlands may be greater than estimated. The reduction of wetlands may affect negatively several species that depend directly or indirectly the resources available in these areas.